Ostraca from the Temple of Millions of Years of Thutmose III - Hagen, Fredrik (Culture and History of the Ancient Near East, 2021)
In Ostraca from the Temple of Millions of Years of Thutmose III , Fredrik Hagen publishes a range of texts from recent excavations at Thebes. Although fragmentary, the corpus is one of the richest of its kind in terms of both the number of ostraca and the different types of texts represented, and provides essential new data for anyone interested in ancient Egyptian temples, religion, priests, and social history. The texts shed light on many aspects of life in an Egyptian temple, including the building of the temple, the daily operations of its cult, the organisation and size of the priesthood, types and quantities of offerings, as well as the broader cultural issues of literacy and the transmission of literature.